2012
DOI: 10.1016/j.bbadis.2012.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Toxic effects of expanded ataxin-1 involve mechanical instability of the nuclear membrane

Abstract: Ataxin 1 (ATXN1) is the protein involved in spinocerebellar ataxia type 1, one of nine dominantly inherited neurodegenerative diseases triggered by polyglutamine expansion. One of the isolated polyglutamine tracts properties is to interact with lipid bilayers. Here we used a multidisciplinary approach to test whether one of the mechanisms responsible for neuronal degeneration involves the destabilization of the nuclear membrane. We thus analyzed the interaction between ATXN1 and lipid membranes, both on cellul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…A convergence of recent evidence has implicated errors in nucleo/cytoplasmic transport as a component of normal aging [11] as well as several neurodegenerative disorders [13], including ALS/FTD [8, 49], Huntingtonā€™s disease (Cleveland and Lagier-Tourenne, personal communication) [35, 43, 68], and other repeat expansion models [38, 51]. Studies in yeast [27] and flies [61] have identified components of nuclear transport as modifiers of toxicity in models expressing mutant TDP-43, or the C9orf72 hexanucleotide repeat expansion [17, 71].…”
Section: Discussionmentioning
confidence: 99%
“…A convergence of recent evidence has implicated errors in nucleo/cytoplasmic transport as a component of normal aging [11] as well as several neurodegenerative disorders [13], including ALS/FTD [8, 49], Huntingtonā€™s disease (Cleveland and Lagier-Tourenne, personal communication) [35, 43, 68], and other repeat expansion models [38, 51]. Studies in yeast [27] and flies [61] have identified components of nuclear transport as modifiers of toxicity in models expressing mutant TDP-43, or the C9orf72 hexanucleotide repeat expansion [17, 71].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, impaired nucleocytoplasmic transport and nuclear integrity have been identified as hallmarks of aged neurons (Fifkova et al, 1987, Mertens et al, 2015). A flurry of recent reports has indicated that nucleocytoplasmic compartmentalization is also markedly impaired in several models of repeat expansion disorders (Chapple et al, 2008, Mapelli et al, 2012, Freibaum et al, 2015, Jovicic et al, 2015, Kaneb et al, 2015, Liu et al, 2015, Rodriguez et al, 2015, Zhang et al, 2015, Da Cruz and Cleveland, 2016, Lee et al, 2016, Nekrasov et al, 2016, Woerner et al, 2016, Zhang et al, 2016, Shi et al, 2017). Furthermore, apparent disruption of the nuclear envelope or disrupted nucleocytoplasmic transport has been reported in postmortem tissues from ALS (Kinoshita et al, 2009), Parkinsonā€™s (Liu et al, 2012) and Alzheimerā€™s disease patients (Sheffield et al, 2006), and in cells expressing aggregation-prone proteins (Frost et al, 2016, Woerner et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The nuclear pore complex (NPC) is the regulated gateway for trafficking between the cell cytosol and nucleus, and is a potential target of mutant polyQ-huntingtin protein in HD 10 , where progressive disruption of nuclear envelope morphology has been observed in aging mice expressing the polyQ-huntingtin protein 9 . Post-mortem samples from patients with ALS 52 also show disruptions to the nuclear envelope, whereas polyQ-ataxin-1 may also decrease nuclear membrane instability 53 . Among the nucleoporins, the main components of NPC, NUP98 has the most conserved FG-dipeptide motif domain and is a major contributor to the NPC permeability barrier 54 .…”
Section: Resultsmentioning
confidence: 99%